2020
DOI: 10.1186/s10194-020-01143-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional assessment of the effects of erenumab in chronic migraine patients with previous unsuccessful preventive treatments: a comprehensive real-world experience

Abstract: Background: erenumab was safe and effective in clinical trials for the prevention of migraine. However, real-life data are still lacking. Here we report the clinical experience from an Italian real-world setting using erenumab in patients with chronic migraine experiencing previous unsuccessful preventive treatments. Methods: Seventy patients with chronic migraine and failure to ≥4 migraine preventive medication classes initially received monthly erenumab 70 mg s.c. Patients without a clinically meaningful imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
127
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 71 publications
17
127
1
10
Order By: Relevance
“…All converters withhold medication overuse. The high rate of conversion to EM in our population of di cult-to-treat patients with a long history of CM and multiple prior preventive treatment failures, including botulinum toxin in ≥ 40% of cases, supports the e cacy of erenumab for the preventive treatment of patients with CM, as shown in randomized controlled trials [13][14][15][16][17][18] and real-life studies [7][8][9][10]. We also found that at Months 4-6 16.5% of patients achieved a status of LFEM, while 28.6% achieved a status of MFEM, which indicates a high treatment bene t and a substantial improvement in the patients' quality of life.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…All converters withhold medication overuse. The high rate of conversion to EM in our population of di cult-to-treat patients with a long history of CM and multiple prior preventive treatment failures, including botulinum toxin in ≥ 40% of cases, supports the e cacy of erenumab for the preventive treatment of patients with CM, as shown in randomized controlled trials [13][14][15][16][17][18] and real-life studies [7][8][9][10]. We also found that at Months 4-6 16.5% of patients achieved a status of LFEM, while 28.6% achieved a status of MFEM, which indicates a high treatment bene t and a substantial improvement in the patients' quality of life.…”
Section: Discussionmentioning
confidence: 57%
“…Monoclonal antibodies directed against the calcitonin gene-related peptide (CGRP) or its receptor (CGRPr) are migraine-speci c treatments whose e cacy and safety were proven in both EM and CM [2][3][4][5]. However, the available real-life studies show that most patients treated in common clinical practice have CM [6][7][8][9][10]. In the present real-life, multicenter study, we assessed the rate and possible predictors of conversion from CM to EM in patients treated with erenumab.…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, however, this may have inadvertently diminished the potential clinical value of assessing the impact of a treatment on the combination of frequency, severity, and duration of pain associated with migraine that may be more closely associated with the patient's overall pain experience [19,20]. Moreover, other "real-world" assessments of migraine include a variety of patient-reported outcomes (e.g., disability and quality of life) to fully assess the potential bene t of migraine treatment strategies [21,22]. Total pain burden may better re ect what clinicians and patients discuss regarding the individual's pain experience and could prove useful to further patient-centric discussions regarding treatment expectations when clinicians are evaluating options for migraine prevention.…”
Section: Discussionmentioning
confidence: 99%
“…All converters withhold medication overuse. The high rate of conversion to EM in our population of di cult-to-treat patients with a long history of CM and multiple prior preventive treatment failures, including botulinum toxin in ≥40% of cases, supports the e cacy of erenumab for the preventive treatment of patients with CM, as shown in randomized controlled trials [17][18][19][20][21][22] and real-life studies [10][11][12][13]. We also found that at Months 4-6 16.5% of patients achieved a status of LFEM, while 28.6% achieved a status of MFEM, which indicates a high treatment bene t and a substantial improvement in the patients' quality of life.…”
Section: Discussionmentioning
confidence: 59%